Tasawuf Enterpreneurship - Muhamad Ali Tamrin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Sufism should not be implied to the activity oriented to activities away from the world. Sufism should be used as a spirit to every Muslim to accumulate wealth in the world. However, the world's wealth is eventually used to struggle to collect charity for the hereafter. Prophetic Intelligence is the study of mysticism that can be used to integrate the interests of the world and the hereafter. The practice of prophetic intelligence is referring to the example of the Prophet Mohammad SAW. One side as the Prophet, He expands the task of for hereafter issues. In the other side as a trader, he exemplifies efforts to become entrepreneurs in the world. The example of the Prophet Muhammad is an example of ethical entrepreneurship.